Lateral versus posterior quadratus lumborum block in children undergoing open orchiopexy: a double-blind randomized clinical trial - Ozgecan P. Zanbak Mutlu; Pinar Kendigelen; Ayse C. Tutuncu (Brazilian Journal of Anesthesiology)
Background: Quadratus Lumborum Block (QLB) has recently become an effective analgesic regional technique frequently used in abdominal surgeries. However, due to the heterogeneity in studies regarding block approaches, a direct comparison of QLB types is needed. In this double-blind prospective randomized trial, we aimed to compare the effects of lateral and posterior approaches of QLB on pain and analgesic use in children undergoing orchiopexy. Methods: Patients aged 6 months – 12 years undergoing elective unilateral open orchiopexy were included in the study. Patients were randomized into two groups using the closed-envelope method. Lateral or posterior QLB was applied under ultrasonography with 0.4 mL/kg 0.25% bupivacaine for both groups before the surgery. The primary outcome was the assessment of postoperative pain for 24 hours. Analgesic usage, parental satisfaction, and complications were recorded as secondary outcomes. Results: Analyses were conducted on 80 patients. Both study groups achieved clinically adequate analgesia, and no significant pain score distinctions were observed within 24 hours (Total mean scores: FLACC [lateral QLB: 2.86 ± 4.69 vs. posterior QLB: 2.87 ± 3.71, p = 0.466], Wong-Baker [lateral QLB: 0.86 ± 2.03 vs. posterior QLB: 1.24 ± 1.85, p = 0.151]). No significant interaction effect between groups and postoperative time intervals on pain scores was observed (FLACC score p-interaction: 0.425, Wong-Baker score p-interaction: 0.451). There were no statistical differences in the number of patients necessitating intraoperative and postoperative analgesics. Parental satisfaction exhibited similarity between the groups, and no perioperative complications were observed in either group. Conclusion: Lateral and posterior QLB provided similar perioperative analgesia in pediatric patients undergoing orchiopexy. Clinical trial registration number: NCT05056038. Date of registration: 02 June 2021.